PENDEKATAN MAQÂSHID AL- SYARI’AH DALAM PEMIKIRAN ALI JUM’AH - Sugianto, David; Salma, Salma (Jurnal AL-AHKAM, 2020)
The  problem  of  this  research  is  how  to  approach  and  apply  maqâshid  al-syari'ah  in thinking  of  Ali  Jum'ah.  Starting  from  the  approach  of  maqâshid  al-shariah  in  maintaining  the benefit of religion (hifz al-din), maintaining the benefit of the soul (hifz an-nafs), maintaining the welfare  of  the  mind  (hifz  al-'aql),  maintaining  the  benefit  of  the  descend  /  nasab  (hifz  an-nasl) and  preserves  the  wealth  of  property  (hifz  al-mâl).The  purpose  achieved  in  this  research  is  to know the application of maqâshid al-syari'ah by Ali Jum'ah in thought and view and his opinion in  establishing  Islamic  law.  The  extent  to  which  maqâshid  al-shari'ah  is  applied  in  terms  of maintaining the good of the religion  (hifz al-din), preserving the soul's goodness  (hifz an-nafs), maintaining the welfare of the mind (hifz al-'aql), maintaining the good of the descendants (hifz- nasl)  and  maintain  the  wealth  of  property  (hifz  al-mal).This  research  is  a  study  character  of library  research  (library  research).  The  main  source  of  this  research  is  the  book  al-Kalim  al- Thayyib  Fatawa  'Ashriyah  and  Fatawa  Bait  al-Muslim,  is  a  book  written  by  Ali  Jum'ah.  Other supporting sources include other Ali Jum'ah books such as Aliyat al-Ijtihâd, Madkhal ila Dirasah al-Mazâhib  al-Fiqhiyah,  Madkhal  fi  al-Thurâst,  al-Qiyâs'  Inda  Ushuliyyin,  and  other  books  by others  support  and  refine  this  research.The  results  of  this  study  can  be  concluded  that  some thoughts  and  fatwa  of  Ali  Jum'ah  when  associated  with  maqâshid  al-syari'ah  (the  purpose  of legal pensyariatan) in the five elements that exist; keeping religion, soul, mind, descendant, and treasure,  apparently  has  a  common  point  in  its  application.One  of  the  thoughts  of  Ali  Jum'ah with  the  approach  of  maqâshid  al-syari'ah  in  the  element  of  maintaining  the  benefit  of  religion (hifz  al-din)  is  about  pilot  fasting  in  Ramadan.  Ali  Jum'ah  says  if  conditions  allow  for  fasting, then may choose between fasting and not fasting. But if conditions are very difficult to fast that can  bring  harm,  then  obliged  to  break  (not  fasting)  and  forbidden  fasting.  In  maintaining  the benefit  of  the  soul  (hifz  an-nafs)  there  are  cases  concerning  the  law  of  organ  transplantation. According to Ali Jum'ah, both transplants from humans who live to other living human beings, as well as corpse organs to living humans are allowed by shari'ah if they meet certain conditions. In maintaining  the  benefit  of  reason  (hifz  al-'aql)  the  author  finds  the  approach  of  maqâshid  al- syari'ah on his fatwa and his thoughts when asked the law of narcotics. Ali Jum'ah only describes the  laws  and  postulates  of  the  Qur'an  and  Sunnah  regarding  the  law  of  khamar,  without harmonizing the connection of narcotics and khamar. In maintaining the benefit of offspring (hifz an-nasl)  the  author  finds  the  maqashid  al-shari'ah  approach  on  the  fatwa  on  the  law  of sterilization  in  humans.  According  to  Ali  Jum'ah,  such  sterilization  is  haram,  if  not  in  an emergency or dangerous. A person is not required to do so if it does not harm him or does not inflict  damage  on  him.  As  for  maintaining  the  wealth  of  property  (hifz  al-mâl)  one  example  of maqâshid al-syari'ah approach to the sale and purchase of land but not face to face between the seller and the buyer. In this case, Ali Jum'ah advised against buying and selling in this condition, for fear of greater harm and wasted loss and futility.Keyword; Ali Jum'ah, Maqâshid Al-Syari’ah, Approach